Changes in the water retention of mountainous landscapes since the 1820s in the Austrian Alps - Stecher, Gabriel; Hohensinner, Severin; Herrnegger, Mathew (Frontiers in Environmental Science, 2023)
Interactions of humans with the environment are strongly related to land use and land cover changes and the available ecosystem services. In last decades, these changes have led to a degradation of ecosystem services, including water regulation and flood control. In the Alpine areas of Austria, land cover changes have increased flood risk since the mid of the 19 th century. In this paper, we assess the influence of these longterm land use changes on the landscape's ability to retain water using the qualitative Water Retention Index (WRI). The changes are thereby evaluated using on the basis of the historical (1826-1859) and present (2016) land cover situation, which is to our knowledge the first high-resolution and regional application of the WRI. The resultsshow that the water retention potential mimics the mountainous characteristic and features. Except for areas strongly dominated by settlement areas, the highest retention potentials are found in valley floors and the lowest values are depicted along the Alpine main complex. In low-lying areas, the retention decreased by over 10 %. It was found that this decrease can be mostly attributed to settlement expansion. Above 1250 m land use transformations led to slightly increasing water retention values owing to the transformation of wasteland or glaciers to stagnant waters and to the expansion of forest and grassland in high elevations. This examination allows for a holistic and spatially distributed LULCC impact assessment on the landscape's water regulation capacities and offers valuable high-resolution information for future land use planning and sustainable land development.